Chip-to-chip communication using a single flux quantum pulse. - Maezawa, M. (IEEE Transactions on applied superconductivity)
Chip-to-chip propagation of a single flux quantum (SFQ) pulse has been demonstrated using an active multichip module (MCM) technique in which active transmitters and receivers are integrated on an MCM substrate as well as on a chip. A chip-to-chip SFQ transfer circuit has been designed and implemented by a standard Nb-trilayer process and solder-bumped flip-chip technology. The correct operation of the circuit has been confirmed by low-frequency testing. Experimental margins for the global factor for bias currents have been as large as ±33%